Respostas
respondido por:
7
576/2
288/2
144/2
72/2
36/2
18/2
9/3
3/3
1
288/2
144/2
72/2
36/2
18/2
9/3
3/3
1
respondido por:
5
√(576)
Fatorando
576 |2
288 |2
144 |2
72 |2
36 |2
18 |2
9 |3
3 |3
1
Substituindo na raiz
√[(2^2)•(2^2)•(2^2)•(3^2)]
=√(2^2)•√(2^2)•√(2^2)•√(3^2)
=√(4)•√(4)•√(4)•√(9)
=2•2•2•3
=24
Espero ajudar... (:
Fatorando
576 |2
288 |2
144 |2
72 |2
36 |2
18 |2
9 |3
3 |3
1
Substituindo na raiz
√[(2^2)•(2^2)•(2^2)•(3^2)]
=√(2^2)•√(2^2)•√(2^2)•√(3^2)
=√(4)•√(4)•√(4)•√(9)
=2•2•2•3
=24
Espero ajudar... (:
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás